Fostering innovative work behavior of employees in the tourism industry: Strategies for successful remote tourism during the COVID-19 pandemic - Taufiqur Rachman; Rina Anindita; Nabila Noor Izmi; Cristofer Ewaldo; Fitriana Rezki; Emanuela Tasya Andini (Jurnal Manajemen dan Pemasaran Jasa, 2022)
Due to the COVID-19 Pandemic, in September 2020, the number of domestic and foreign tourists visiting Indonesia decreased by 88.9% to 153,498 people from 1.38 million people in the same period in 2019. The Research Objective is to examine the effect of Employee Engagement on Innovative Work Behavior, which requires Creativity as a mediator, and the effect of Remote Working as a moderator in the Tourism Service Industry. The study was carried out with the survey method using online questionnaires distributed from January 2022 to February 2022. The participants in this study are practitioners in the tourism service industry who are also members of the Indonesian Tourism Industry Association (GIPI). The participants came from 55 cities in Indonesia and worked remotely during the pandemic. First, this study shows good engagement with the employee does not increase innovative work behavior directly. Second, good employee engagement can increase creativity from the employee. Third, good employee creativity can foster innovative work behavior. Fourth, remote working does not moderate the correlation between employee engagement and creativity. Fifth, employee creativity mediates the correlation between employee engagement and innovative work behavior.